2021
DOI: 10.1101/2021.11.14.21266294
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inactivated virus vaccine BBV152/Covaxin elicits robust cellular immune memory to SARS-CoV-2 and variants of concern

Abstract: The characteristics of immune memory established in response to inactivated SARS-CoV-2 vaccines remains unclear. We determined the magnitude, quality and persistence of cellular and humoral memory responses up to 6 months after vaccination with BBV152/Covaxin. Here, we show that the quantity of vaccine-induced spike- and nucleoprotein-antibodies is comparable to that following natural infection and the antibodies are detectable up to 6 months. The RBD-specific antibodies decline in the range of 3 to 10-fold ag… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“… 13 , 16 An earlier study in adults vaccinated with BBV152 reported cross-reactive T-cell responses to several SARS-CoV-2 variants (alpha, beta, and delta). 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 13 , 16 An earlier study in adults vaccinated with BBV152 reported cross-reactive T-cell responses to several SARS-CoV-2 variants (alpha, beta, and delta). 20 …”
Section: Discussionmentioning
confidence: 99%
“…Vikkurthi and colleagues, also show (in a preprint) that, ex vivo, BBV152-generated T cells (Tfh) assist in B-cell production of antibodies against SARS-CoV-2 variants of concern. 20 …”
Section: Discussionmentioning
confidence: 99%
“…COVAXIN® was found to induce robust immune memory and Th1 skewed response in previous studies. 23,24 The vaccine was also found to elicit a substantial fraction of T follicular cells which in turn can aid in long term humoral immunity. 23 The proportion of the antibody secreting memory B cells in the 3 dose COVAXIN® recipients were found more compared to the 2 dose recipients.…”
Section: Discussionmentioning
confidence: 99%
“…10,20 Apart from B cell mediated immunity, the SARS-CoV-2 specific central and effector memory cells which can aid in cytotoxic function (CD8+ TEMRA phenotype) has been demonstrated in the COVAXIN® recipients. 23 These properties could have attributed to the rapid reduction of viral load after challenge. Although marked difference was not observed in the histopathological cumulative score of the BA.1.1 infected groups, the mean score of the vaccinated groups were considerably lower compared to our earlier studies on pathogenicity of BA.1.1 in hamster.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation